Pengembangan Konten Podcast Edukatif Mata Pelajaran Bahasa Indonesia Materi Puisi MTS DDI Jarasua di Kabupaten Soppeng - Mubarak, Fadil; Arnidah, Arnidah; Sinaga, Andromeda Valentino (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify the need for using educational Podcast content in Indonesian language subjects, design poetry-themed educational Podcast content, and describe the level of validity and practicality of the developed product at MTs DDI Jarasua, Soppeng Regency. The method used is the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The results of the study indicate that educational Podcast content is highly needed by students in learning poetry. Product feasibility assessments showed that it was highly valid based on content/material expert validation and media expert validation. The small group trial showed the product was practical, while the large group trial showed it was highly practical. In conclusion, the developed poetry-themed educational Podcast content is valid and practical for use in poetry learning for eighth-grade students at MTs DDI Jarasua.